Biological applications of xeno nucleic acids. Issue 2 (9th November 2016) - Morihiro, Kunihiko; Kasahara, Yuuya; Obika, Satoshi
Abstract : Xeno nucleic acids (XNAs) are a group of chemically modified nucleic acid analogues that have been applied to various biological technologies such as antisense oligonucleotides, siRNAs and aptamers. Abstract : Xeno nucleic acids (XNAs) are a group of chemically modified nucleic acid analogues that have been applied to various biological technologies such as antisense oligonucleotides, siRNAs and aptamers.